2022
DOI: 10.14814/phy2.15292
|View full text |Cite
|
Sign up to set email alerts
|

Chronic glucocorticoid exposure causes brown adipose tissue whitening, alters whole‐body glucose metabolism and increases tissue uncoupling protein‐1

Abstract: Adipose tissue (AT) has been found to exist in two predominant forms, white and brown. White adipose tissue (WAT) is the body's conventional storage organ, and brown adipose tissue (BAT) is responsible for non-shivering thermogenesis which allows mammals to produce heat and regulate body temperature. Studies examining BAT and its role in whole-body metabolism have found that active BAT utilizes glucose and circulating fatty acids and is associated with improved metabolic outcomes. While the beiging of WAT is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…In the present experimental model, the BAT of GC-treated rats completely loses its well-known characteristics: there was an increase in mass, changes in morphology to an unilocular phenotype, reduced expression of genes related to thermogenesis/brown adipocytes markers, and most importantly, the decreased oxidative capacity ( Figure 7 a–g), which characterizes a whitening process [ 81 , 82 ]. Our results corroborate with some studies that have shown that GC excess leads to changes in the morphology and/or thermogenic function [ 83 , 84 , 85 , 86 , 87 ]. However, it is still unclear whether BAT dysfunctions are a cause or a consequence of the AT redistribution/obesity that occurs in Cushing’s syndrome, but the BAT whitening may also explain some metabolic changes in this model.…”
Section: Discussionsupporting
confidence: 92%
“…In the present experimental model, the BAT of GC-treated rats completely loses its well-known characteristics: there was an increase in mass, changes in morphology to an unilocular phenotype, reduced expression of genes related to thermogenesis/brown adipocytes markers, and most importantly, the decreased oxidative capacity ( Figure 7 a–g), which characterizes a whitening process [ 81 , 82 ]. Our results corroborate with some studies that have shown that GC excess leads to changes in the morphology and/or thermogenic function [ 83 , 84 , 85 , 86 , 87 ]. However, it is still unclear whether BAT dysfunctions are a cause or a consequence of the AT redistribution/obesity that occurs in Cushing’s syndrome, but the BAT whitening may also explain some metabolic changes in this model.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, the whitened phenotype has not been previously associated with increased uncoupling proteins under chronic stress, however, Bel et al. ( 174 ) suggested that the increased UCP1 expression could be a compensatory mechanism under certain stress.…”
Section: Factors Inducing Bat/beige Adipose Tissue Whitening or Inact...mentioning
confidence: 99%
“…Consistently, UCP1 expression was downregulated, while the expression of WAT marker genes RB transcriptional corepressor 1 (Rb1), nuclear-receptor-interacting protein 1 (Nrip1), and Rbl1/p107 (RB transcriptional corepressor like 1) were upregulated ( 173 ). Other evidence showed that chronic exposure to corticosterone can induce the whitening of BAT in C57BL/6 mice, this was evident by increased adipocyte area and elevated expressions of UCP1 in BAT ( 174 ). Of note, the whitened phenotype has not been previously associated with increased uncoupling proteins under chronic stress, however, Bel et al.…”
Section: Factors Inducing Bat/beige Adipose Tissue Whitening or Inact...mentioning
confidence: 99%
“…This symptomatology is similar to that observed in Cushing’s patients with hypercortisolemia ( 7 ). In rodents, dexamethasone and corticosterone both cause insulin resistance and muscle atrophy ( 8 10 ). Corticosterone induces adiposity, but the effect of dexamethasone on body composition is not as clear, as both loss and gain of total fat mass have been reported ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%